Adherence to European Society of Gastrointestinal Endoscopy Quality Performance Measures for Upper and Lower Gastrointestinal Endoscopy: A Nationwide Survey From the Italian Society of Digestive Endoscopy - Zagari, Rocco Maurizio; Frazzoni, Leonardo; Fuccio, Lorenzo; Bertani, Helga; Crinò, Stefano Francesco; Magarotto, Andrea; Dajti, Elton; Tringali, Andrea; Da Massa Carrara, Paola; Cengia, Gianpaolo; Ciliberto, Enrico; Conigliaro, Rita; et al. (Frontiers in Medicine, 2022)
Background: Quality of gastrointestinal (GI) endoscopy has been recently identified as a major priority being associated with many outcomes and patient experience. Objective: To assess adherence of endoscopists to the European Society of Gastrointestinal Endoscopy (ESGE) quality performance measures for upper and lower GI endoscopy in Italy. Methods: All endoscopists members of the Italian Society of Digestive Endoscopy (SIED) were invited from October 2018 to December 2018 to participate to a self-administered questionnaire-based survey. The questionnaire included questions on demographic and professional characteristics, and on the recent ESGE quality performance measures for upper and lower GI endoscopy. Results: A total of 392 endoscopists participated to the study. Only a minority (18.2%) of participants recorded the duration of esophagogastroduodenoscopy (EGD) and 51% provided an accurate photodocumentation in the minimum standard of 90% of cases. Almost all endoscopists correctly used Prague and Los Angeles classifications (87.8% and 98.2%, respectively) as well as Seattle and MAPS biopsy protocols (86.5% and 91.4%, respectively). However, only 52.8% of participants monitored complications after therapeutic EGD and 40.8% recorded patients with a diagnosis of Barrett’ esophagus. . As regard colonoscopy, almost all endoscopists (93.9%) used the Boston Bowel Preparation Scale for measuring bowel preparation quality and reported a cecal intubation rate ≥ 90%. However, about a quarter (26.2%) of participants reported an adenoma detection rate < 25%, only 52.8% applied an appropriate polypectomy technique, 48% monitored complications after the procedure and 12.4% measured patient’s experience. Conclusions: Adherence of endoscopists to ESGE performance measures for GI endoscopy is sub-optimal in Italy. There is a need to disseminate and implement performance measures and endorse educational and scientific interventions on the quality of endoscopy.